Synthesis, structural and thermal characterizations and in vitro cytotoxic activities of new cyclotriphosphazene derivatives - Koran, Kenan; Tekin, Çiğdem; Çalışkan, Eray; Tekin, Suat; Sandal, Süleyman; Görgülü, Ahmet Orhan (My University, 2017)
We investigated the cytotoxic effects of the newly synthesized cyclotriphosphazene derivatives on A2780 (ovarian), PC-3 and LNCaP (prostate) cancer cell lines. 4?-hydroxy-substituted-chalcone compounds (2–8) were reacted with diphenyl-cyclotriphosphazene (DPP) in the presence of acetone/K2CO3 in order to obtain novel cyclotriphosphazene compounds (DPP 2–8). The structures of DPP 2–8 were characterized by MALDI-TOF mass spectrometry, FT-IR, elemental analysis, 1H, 13C-APT, and 31P NMR measurements. The thermal properties of all phosphazene compounds have been studied after synthesis and characterization procedure. The cytotoxic effects of DPP 2–8 were examined primarily by applying the MTT method based on the measurement of mitochondrial activity. In this regard, several phosphazene compounds have shown high chemotherapeutic effect at low dose (p < 0.05). When the cytotoxic effects of DPP 2–8 at doses of 1, 5, 25, 50 and 100 µM on A2780 cells were examined, it was observed that DPP-3, DPP-4, DPP-5 and DPP-7 were more effective than other derivatives suggested by their high Log IC50 values (p < 0.05). The compounds DPP 2–8 possess cytotoxic activity against PC-3 and LNCaP cells (especially compounds DPP-4 and DPP-5, p < 0.05).
Yeni siklotrifosfazen türevlerinin sentezi, yapısal ve termal karakterizasyonu ve in vitro sitotoksik aktiviteleri
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Cyclotriphosphazene; Cytotoxic activities; Chalcone-phosphazene; Cancer cell lines